First words - Redford, Ruth; Maddocks, Maria (London ladybird, 2015)
Ladybird Toddler Touch First Words is perfect for young children who are starting to explore the world around them. It is full of interesting new words and pictures that are familiar to toddlers, along with interesting finger trails on every page, flaps to lift, and plenty of things to touch and feel
Linguistic notions
1 23
CHILDTHEN
Keywords: Language and Languages